Wini (arm and leg beads) - Unidentified artist (Colorado State University. Libraries, 2016)
Detail of the beads used in winis.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Commercially made glass beads.
Keywords: Molas -- Panama; Beadwork -- Panama